The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.bbapap.2008.04.028
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group proteins and their post-translational modifications

Abstract: The high mobility group (HMG) proteins, including HMGA, HMGB and HMGN, are abundant and ubiquitous nuclear proteins that bind to DNA, nucleosome and other multi-protein complexes in a dynamic and reversible fashion to regulate DNA processing in the context of chromatin. All HMG proteins, like histone proteins, are subjected to extensive post-translational modifications (PTMs), such as lysine acetylation, arginine/lysine methylation and serine/threonine phosphorylation, to modulate their interactions with DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 140 publications
(196 reference statements)
6
81
0
Order By: Relevance
“…Yet these patterns of phosphorylation are not well studied. The high mobility group proteins exhibit modifications similar to histones and are found in association with histones in chromatin (50). Other examples include tubulin (51) and p53 (52).…”
Section: Discussionmentioning
confidence: 99%
“…Yet these patterns of phosphorylation are not well studied. The high mobility group proteins exhibit modifications similar to histones and are found in association with histones in chromatin (50). Other examples include tubulin (51) and p53 (52).…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modifications of HMG proteins can alter their interactions with DNA and proteins, and consequently, affect their biological activities (1). HMGB1, for example, could be phosphorylated and/or acetylated by pro-inflammatory signals and translocated to the cytoplasm for secretion (12,13) to induce proinflammatory response (14,15).…”
Section: High Mobility Group Nucleosomal Binding Domain 2 (Hmgn2)mentioning
confidence: 99%
“…HMG proteins are subject to a wide range of post-translational modifications including acetylation, methylation, SUMOylation, and phosphorylation (1). Post-translational modifications of HMG proteins can alter their interactions with DNA and proteins, and consequently, affect their biological activities (1).…”
Section: High Mobility Group Nucleosomal Binding Domain 2 (Hmgn2)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the shared biochemical properties already noted, the D1 protein is predicted to have extensive intrinsic protein disorder (Uversky et al 2005; data not shown), a demonstrated attribute of HMGA proteins (Lehn et al 1988;Huth et al 1997). Both D1 and HMGA proteins are highly post-translationally modified (Zhai et al 2008;Zhang and Wang 2008). The primary distinction, increased size for D1, is accompanied by a proportional increase in number of AT-hook motifs.…”
Section: Discussionmentioning
confidence: 99%